1983
DOI: 10.1002/ajmg.1320160213
|View full text |Cite
|
Sign up to set email alerts
|

Perrault's syndrome in two sisters

Abstract: We report on two sisters with Perrault's syndrome, i.e., autosomal recessive ovarian dysgenesis associated with sensorineural deafness. They were deaf-mute and of normal height with a few minor somatic anomalies. Both had streak gonads and an apparently normal female 46,XX chromosome constitution. The parents were apparently not consanguineous. The mother had normal hearing. Other relatives were not available for study. Epilepsy, which occurred in three relatives including one of the index patients, may have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…In a report by Bosze et al, 8 body proportions was reported in two siblings. The heights were 160 and 162 cm, arm spans were 162 and 164 cm and US:LS ratios were 0.76:1 and 0.78:1 respectively.…”
Section: Discussionmentioning
confidence: 90%
“…In a report by Bosze et al, 8 body proportions was reported in two siblings. The heights were 160 and 162 cm, arm spans were 162 and 164 cm and US:LS ratios were 0.76:1 and 0.78:1 respectively.…”
Section: Discussionmentioning
confidence: 90%
“…Short stature and variable mental retardation were also reported [Christakos et al, 1969;Perez-Ballester et al, 1970;Pallister and Opitz, 1979;Bösze et al, 1983;McCarthy and Opitz, 1985;Nishi et al, 1998]. Recently, Linssen et al [1994] and Gottschalk et al [1996] focused on the neurological signs in patients with Perrault syndrome (PS).…”
Section: Introductionmentioning
confidence: 94%
“…Since then, 17 patients with Perrault syndrome have been described [Christakos et al, 1969;Perez-Ballester et d., 1970;Pallister and Opitz, 1979;Granat et al, 1979;Bosze et al , 1983;McCarthy and Opitz et al, 19851. Here we report an additional two cases, sisters with this syndrome.…”
Section: Introductionmentioning
confidence: 98%